The Effects of Laurencia caspica Algae Extract on Hemato-Immunological Parameters, Antioxidant Defense, and Resistance against Streptococcus agalactiae in Nile tilapia (Oreochromis niloticus) - Majid Khanzadeh; Babak Beikzadeh; Seyed Hossein Hoseinifar (Aquaculture Nutrition)
Natural immune stimulants are among the most effective chemicals for boosting immunity and fish welfare. This study aims to investigate the effects of red macroalgae extract (Laurencia caspica) on hematological, immunological, antioxidant, biochemical, and disease resistance against S. agalactiae in Nile tilapia for 50 days. For this purpose, fishes were assigned to four dietary treatments group in which the base meal was supplemented with 0.5%, 1%, and 2% of L. caspica extract. On days 25 and 50 of the experiment, samples were taken to investigate the hematological, immunological, biochemical, and antioxidant parameters. The white blood cells (WBCs), hemoglobin, and neutrophils significantly increased after 50 days of feeding with the L. caspica extract, but until the 25th day, no significant difference was observed among the treatments except for hemoglobin. Immunological parameters (including Immunoglobulin M [IgM] and complement 3 [C3]) were significantly higher in treated groups compared to control both 25 days and 50 days posttreatment. However, on the 25th day, no significant difference was noticed between treatments and control in the case of lysozyme activity. Alkaline phosphatase (ALP) and alanine aminotransferase (ALT) considerably increased in comparison to the control group on the 50th day, but no significant difference was observed on the 25th day. In addition, feeding with L. caspica significantly increased the antioxidant enzyme activities on the 25th day (L. caspica 1% and 2% in peroxidase [POD] and superoxide dismutase [SOD] in all groups) and 50th day (catalase [CAT], SOD and L. caspica 1% and 2% in POD) in the spleen. The survival rate of fish challenged with Streptococcus agalactiae was considerably greater than the control group. Finally, it can be concluded that L. caspica extract is an immunological stimulant that induces fish resistance to S. agalactiae.